(untitled) - Krollova, Sandra; Vladar, Adam (Doprava a spoje, 2012)
Aviation personnel are exposed to various degrees of stress and eventual strong emotional situations when fulfilling their duty roles. The response to these stressors could be mitigated by Critical incident stress management. The role of the Critical incident stress management is to accelerate post-traumatic recovery and prevent development of the Post-Traumatic Stress Disorder. It has irreplaceable importance in aviation. Allows the reactivation of the cognitive functions and faster regaining the ability to work after critical incident, contributes to the overall wellbeing of the personnel and to the safety of air transportation not least. This paper was written as a one of scientific results of the project co-financed by EU "Broker centre of air transport for transfer of technology and knowledge into transport and transport infrastructure" ITMS 26220220156.